1991
DOI: 10.1161/01.atv.11.4.882
|View full text |Cite
|
Sign up to set email alerts
|

Activation of calpain I and hydrolysis of calpain substrates (actin-binding protein, glycoprotein Ib, and talin) are not a function of thrombin-induced platelet aggregation.

Abstract: Calcium-activated neutral proteinase (calpain) has been shown to cleave proteins involved in the maintenance of cell structure. In human platelets, substrates of calpain include glycoprotein Ib (GPIb), actin-binding protein (ABP), and talin. GPIb-ABP complexes can be isolated in detergent extracts and are thought to represent membrane-cytoskeleton attachment sites. It has been hypothesized that the hydrolysis of GPIb-ABP by calpain is regulated by the extent of binding of this proteinase to the plasma membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Methods were the same as those described in the legend for Figure 1C except that STAT3 was recognized by the anti-STAT3 MoAb as in Figure 2A. 19,20 a significant loss of STAT5 immunoreactivity was observed ( Figure 1D), resulting in appearance of a major cleaved band (as in Figure 1A). The band was not recognized by anti-STAT5 antibodies reactive with the carboxy-terminal domain of STAT5 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Methods were the same as those described in the legend for Figure 1C except that STAT3 was recognized by the anti-STAT3 MoAb as in Figure 2A. 19,20 a significant loss of STAT5 immunoreactivity was observed ( Figure 1D), resulting in appearance of a major cleaved band (as in Figure 1A). The band was not recognized by anti-STAT5 antibodies reactive with the carboxy-terminal domain of STAT5 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies in different models ranging from the lens of the eye 13 to spinal cord neurons 14 have shown that calpains are important in actin remodeling, and this study extends those observations to cold preserved SEC. Yoshida 13 reported a direct effect of calpain on actin, but calpain is also active against actin-associated proteins such as talin 33 and actin-binding protein 34,35 and localizes in some models to the site on the cell membrane where these proteins are present. 34 Therefore, the effect of calpain on actin disassembly may be partly or entirely indirect, i.e., actin disassembly may be induced by degradation of actin-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…2A by using [32P]VASP overlays as a detection tool. Detection of the VASP-binding protein p83 was strongly dependent op the presence of a specific fibrinogen receptor (integrin a1nb33) antagonist or on high concentrations of a Ca2+ chelator during platelet preparation or platelet lysis, respectively (not shown), suggesting that p83 is susceptible to platelet aggregationdependent proteolysis by calpain (21,22). In a first chromatographic step VASP-binding activity was recovered at neutral pH in the 70-220 mM NaCl eluate of a cation exchanger (S-Sepharose FF) and was nearly quantitatively precipitated by the addition of ammonium sulfate (30% saturation).…”
Section: Methodsmentioning
confidence: 99%